Health literacy of patients with chronic diseases – quantitative results of a mixed methods study in primary healthcare / Gesundheitskompetenz von Menschen mit chronischer Erkrankung – quantitative Ergebnisse einer Mixed-Methods-Studie in der Primärversorgung - Nock Annike Morgane; Petersen-Ewert Corinna; Jürgensen Ivonne-Nadine; Metzing Sabine (International Journal of Health Professions)
In research and practice to promote health literacy, people with chronic illnesses represent an important target group. They are confronted with complex demands during the course of their illness. And, they utilize healthcare services more frequently. Patients are often dependent on the support of healthcare professionals. Population-based studies in Germany conducted that the majority of people find it most difficult to assess health information. The studies emphasize the enhancement of professional‘s health literacy, e. g. in nursing profession, as a prerequisite for improving capabilities in the population. In order to achieve better access and a needs-based care for people with chronic illnesses, a project in northern Germany has developed and offered a care-led concept.